Edgar Allan Poe : the critical heritage - Walker, I. M. (Ian Malcolm) (Critical heritage series., 1997)
This set comprises 40 volumes covering nineteenth and twentieth century European and American authors. These volumes will be available as a complete set, mini boxed sets (by theme) or as individual volumes. This second set compliments the first 68 volume set of Critical Heritage published by Routledge in October 1995.